Internal Marketing in Car Transport Companies: An Empirical Study - Mariusz WOŹNIAKOWSKI (Communications of International Proceedings, 2022)
The article aims to present the possibilities and scope of the use of online tools in the communication of transport companies with employees working as drivers. Such activities fit into the concept of marketing 4.0, according to which in the era of digital marketing shaped by the IT revolution, the level of consumer involvement (human-centric marketing) has significantly changed, so it can be assumed that it will affect internal marketing, the element of which will be efficient, engaging and building of relations between the company's communication system and its employees. The theoretical basis is a literature study of the described issue. The empirical part presents the results of own research. The author's research carried out under the research project "Logistics processes in marketing activity". The survey was carried out in April 2018 using the method of an Internet survey among users (managers of transport companies and drivers) using the Trans.eu electronic transport exchange. The selected aspects of the research carried out among car transport companies cited in this article show that companies use Internet communication tools relatively widely, and among the motivations for their use from the point of view of management, there are those related to internal marketing. On the other hand, employees expect actions aimed at internal communication. Among the surveyed entities, the biggest problem turned out to be the dissemination of information about the used communication tools on the Internet as part of internal activities.
Keywords: Internal Marketing; Internal Public Relations; Internal Communication.